Mutations in MYO9B are associated with Charcot–Marie–Tooth disease type 2 neuropathies and isolated optic atrophy. (21st November 2022) - Cipriani, Silvia; Guerrero‐Valero, Marta; Tozza, Stefano; Zhao, Edward; Vollmer, Veith; Beijer, Danique; Danzi, Matt; Rivellini, Cristina; Lazarevic, Dejan; Pipitone, Giovanni Battista; Grosz, Bianca Rose; Lamperti, Costanza; et al.
Abstract: Background and purpose: Charcot–Marie–Tooth disease (CMT) is a heterogeneous group of disorders caused by mutations in at least 100 genes. However, approximately 60% of cases with axonal neuropathies (CMT2) still remain without a genetic diagnosis. We aimed at identifying novel disease genes responsible for CMT2. Methods: We performed whole exome sequencing and targeted next generation sequencing panel analyses on a cohort of CMT2 families with evidence for autosomal recessive inheritance. We also performed functional studies to explore the pathogenetic role of selected variants. Results: We identified rare, recessive variants in the MYO9B (myosin IX) gene in two families with CMT2. MYO9B has not yet been associated with a human disease. MYO9B is an unconventional single‐headed processive myosin motor protein with signaling properties, and, consistent with this, our results indicate that a variant occurring in the MYO9B motor domain impairs protein expression level and motor activity. Interestingly, a Myo9b ‐null mouse has degenerating axons in sciatic nerves and optic nerves, indicating that MYO9B plays an essential role in both peripheral nervous system and central nervous system axons, respectively. The degeneration observed in the optic nerve prompted us to screen for MYO9B mutations in a cohort of patients with optic atrophy (OA). Consistent with this, we found compound heterozygous variants in one case with isolated OA. Conclusions: Novel or very rare variants in MYO9B are associated with CMT2 and isolated OA.